SEXING OF IN VITRO PRODUCED PREIMPLANTATION BUFFALO EMBRYOS BASED ON EARLY CLEAVAGE RATE - GOPIKRISHNAN, D; SRIDEVl, P; BALASUBRAMANIAN3, S; KUMANAN, K; REENA, D (The Indian Journal of Animal Reproduction, 2023)
The present study aimed to determine the sex of in vitro produced preimplantation buffalo embryos inrelation to the time of first cleavage, by polymerase chain reaction (PCR). Abattoir derived buffalo oocytesfertilized in vitro were monitored from 18 hours post insemination (hpi) to establish the time of first cleavage.The early cleaved 2-cell embryos were collected at specific time points viz. 18, 24 and 36 hpi, snap frozenand sexed to study the time of cleavage versus sex of in vitro produced buffalo embryos. Of the 113 embryoscleaved, the percentage of embryos that cleaved at 18, 24 and 36 hpi was 2.65, 6.19 and 91.15, respectively.The percentage of male and female embryos that cleaved at 18, 24, and 36 hpi were 66.67 and 33.33, 50 and50, and 40 and 60, respectively. Thus, it could be concluded that the time of first cleavage in buffalo embryosoccurred as early as 18 hpi with male embryos cleaving at a faster rate than the female embryos.
Keywords: Sex; Cleavage rate; Preimplantation; Buffalo embryos